What explains the gender earnings gap in self-employment? A decomposition analysis with German data - Daniel S. J. Lechmann; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2012)
Using a large data set for Germany, we show that both the raw and the unexplained gender earnings gap are higher in self-employment than in paid employment. Applying an Oaxaca-Blinder decomposition, more than a quarter of the difference in monthly self-employment earnings can be traced back to women working fewer hours than men. In contrast variables like family background, working time flexibility and career aspirations do not seem to contribute much to the gender earnings gap, suggesting that self-employed women do not earn less because they are seeking work-family balance rather than profits. Differences in human capital endowments account for another 13 percent of the gap but segregation does not contribute to the gender earnings gap in a robust way. – – Mit einem großen Datensatz für Deutschland zeigen wir, dass sowohl der gesamte geschlechtsspezifische Verdienstunterschied als auch dessen unerklärter Teil bei Selbständigen größer ausfallen als bei abhängig Beschäftigten. Gemäß einer Oaxaca-Blinder-Zerlegung ist über ein Viertel des Unterschieds im Monatsverdienst von Selbständigen darauf zurückzuführen, dass Frauen kürzere Arbeitszeiten haben als Männer. Dagegen scheinen Variablen wie Familienhintergrund, Arbeitszeitflexibilität und Karriereaspiration nicht substanziell zum Geschlechter-Verdienstdifferenzial beizutragen. Dies legt nahe, dass selbständige Frauen nicht deshalb weniger verdienen, weil sie eher an der Vereinbarkeit von Arbeit und Familie und weniger an Gewinnerzielung interessiert sind. Unterschiede in der Humankapitalausstattung erklären weitere 13 Prozent des Differenzials, doch Segregation spielt keine eindeutige Rolle.
Keywords: J31; J71; 330; earnings differential; entrepreneurship; gender pay gap; Germany; self-employed; self-employment